On the Possibility of Implementing CCS Projects in the Carbonate Reservoirs of the Siberian Platform; Theoretical Foundations of Chemical Engineering; Vol. 58, iss. 4 - Nikitenkov A. N. Aleksey Nikolaevich; Novikov D. A. Dmitry Anatoljevich; Maksimova A. A. Anastasiya Alekseevna; Penigin A. V. Artem Vitaljevich; Varaksina I. V. Irina Valerjevna; Zhukovskaya E. A. Elena Anatoljevna (2024, 2024)
Title screen